Clinical practice guidelines adherence, knowledge and awareness in rare and complex connective tissue diseases across Europe: results from the first ERN ReCONNET survey. Issue 2 (5th September 2020) - Talarico, Rosaria; Marinello, Diana; Bombardieri, Stefano; Burmester, Gerd; Fonseca, Joao; Frank, Charissa; Galetti, Ilaria; Hachulla, Eric; Houssiau, Frederic; Mueller-Ladner, Ulf; Schneider, Matthias; Smith, Vanessa; et al.
Abstract : Introduction: The European Reference Network (ERN) ReCONNET is the ERN aimed at improving the management of rare and complex connective tissue and musculoskeletal diseases (rCTDs) across the European Union (EU). In the mission of ERN ReCONNET, clinical practice guidelines (CPGs) play a crucial role, representing a valid tool towards the harmonisation of the management of rCTDs while improving effectiveness and quality of care delivered to patients. Methods: ERN ReCONNET developed two surveys to map the adherence to rCTDs CPGs among healthcare providers and to assess the knowledge and awareness of CPGs for their diseases among patients, family members and caregivers. Results: The results of the surveys highlighted that healthcare professionals find it useful to apply CPGs in clinical practice (93%), while 62% of them experience difficulties and barriers in the application in their centres. Healthcare professionals also highlighted the need to develop CPGs for all rCTDs and to implement the use of the existing CPGs in clinical practice. On the other hand, patients, families and caregivers are relatively aware of the purpose of CPGs (51%) and 62% of them were aware of the existence of CPGs for their disease. Patient-friendly versions of CPGs and patients' lifestyle guidelines should be systematically developed contributing to the empowerment of patients in the disease management. Conclusion: ERN ReCONNET is addressing the main issues identified in the results of the survey, promoting practical actions for the local adaptation of CPGs across Europe, improving their routine clinical use and increasing the awareness on CPGs among rCTDs patients, family members and caregivers.